PENGARUH PEMBERIAN KOMPENSASI DAN DISIPLIN TERHADAP KINERJA GURU SMK MUHAMMADIYAH 2 PEKANBARU - Liza Oktaviana; Sumarno Sumarno; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to determine the influence of the influence of giving compensation and discipline on the teacher performance SMK Muhammadiyah 2 Pekanbaru. The population in this research is teacher SMK Muhammadiyah 2 Pekanbaru that is as many as 33 teacher. Measurement data using documentation and questionnaire. The data analysis used is multiple linear regression. The results showed that the interest of compensation and discipline have a significant effect on teacher performance. Judging from the calculation of R2 (R Square Change) obtained value of 0.631. This means that the contribution of the influence of learning interest and learning facilities on learning achievement is 63.1%, while the remaining 36.9% influenced by other factors outside research such as work motivation, work environment and so forth. Partial compensation has a positive effect on teacher performance of 0.502, while partial discipline has an effect on performance of 0.327.Key Words: Compeensation, Discipline, teacher performance